2022
DOI: 10.1177/17511437221108905
|View full text |Cite
|
Sign up to set email alerts
|

An Intensive Care Unit peer support group: Participants’ views on format, content and the impact on recovery journeys

Abstract: Background Peer support groups reduce psychological morbidity and increase social support for Intensive Care Unit (ICU) survivors. Group formats differ and research, although emerging, is limited. This study explores a continuously running ICU Expert by Experience group, which has a dual role of support and service-user consultative, from attendees’ perspectives. Methods A thematic analysis was conducted on interviews with current and past members of an ICU Expert by Experience group. 11 participants took part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Studies conducted after the Covid‐19 pandemic found that ICU follow‐up may have greater success with recruitment through virtual models 31 . However, these findings were based on general follow‐up, and Clarke et al's 32 findings suggest that participants prefer meeting peers in person. Most studies have not addressed the issues of the content and setting of peer support meetings, and such meetings were structured differently depending on whether they were an integrated part of a rehabilitation programme 13,33,34 or café‐style informal drop‐in meetings with smaller groups of patients 16 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies conducted after the Covid‐19 pandemic found that ICU follow‐up may have greater success with recruitment through virtual models 31 . However, these findings were based on general follow‐up, and Clarke et al's 32 findings suggest that participants prefer meeting peers in person. Most studies have not addressed the issues of the content and setting of peer support meetings, and such meetings were structured differently depending on whether they were an integrated part of a rehabilitation programme 13,33,34 or café‐style informal drop‐in meetings with smaller groups of patients 16 .…”
Section: Discussionmentioning
confidence: 98%
“…16 However, one study evaluating the format, content and impact of a peer support group found that one specific model of peer support was unlikely to fit all, because support needs change throughout the recovery process. 32 In our study, the café meetings accommodated between 17 and 35 participants. Most participants expressed that listening to numerous perspectives increased their opportunities for identification because of the broad variation in nuances in the patients' and relatives' experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information could help other researchers and clinicians to devise services to implement these strategies. Several methods could be considered including patient led strategies, services directed by healthcare professionals [ 24 ], exercise and rehabilitation classes [ 33 ], patient manuals [ 34 ], digital health [ 35 ], ICU diaries [ 36 , 37 ], visiting ICU [ 34 ], support groups [ 38 ] or a combination of these.…”
Section: Discussionmentioning
confidence: 99%